Pembinaan Membangun Jiwa Entrepreneur Serta Business Plan Pada Remaja Yang Putus Sekolah di Kecamatan Sumbawa - Muammar Khadafie; Jasardi Gunawan; Edi Irawan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The main objective of this community empowerment activity is to build the spirit of developing entrepreneurs and business plans for teenagers who drop out of school in Sumbawa District. The methods used in this community service activity are tutorial methods, mentoring methods, discussion methods and evaluation. The results achieved from this activity are: (1) PKBM HATTA students are enthusiastic about starting an early business, (2) PKBM HATTA students can analyse business opportunities, (3) PKBM HATTA students can understand business development strategies, (4) PKBM HATTA students are able to plan businesses and manage risk management, (5) PKBM HATTA students are able to understand and run briefly related to online marketing management.